PEDAGOGICAL COURSE PROJECTS: AN INTERPRETATION THROUGH THE KNOWLEDGE MATRIX - Ana Rita Levandovski; Marinez Meneghello Passos; Roberta Negrão de Araújo; Sergio de Mello Arruda (Instituto Federal de Mato Grosso, 2021)
This article analyzes three Pedagogical Course Projects (PPC) in the area of Biological Sciences through a research instrument called Matrix of Knowledge - M(S). The methodological procedures were based on Discursive Textual Analysis (ATD). The vertical and horizontal readings of the M(S) Matrix revealed, respectively, the following distributions of the analyzed excerpts: 77.2% were in column 3 (teaching) and 85.5% were allocated in the first line (epistemic). Data analysis also revealed an important gap: it is the absence of excerpts in column 2 of the M(S), dedicated to the determinations of knowledge in relation to teacher learning. This is a worrying result, as the PPCs do not mention or provide considerations for teachers about how to conduct their classes (methodological aspects), how to think about content perspectives (epistemic aspects), finally, how to develop the conditions of the teaching action.